DAMPAK PROGRAM “KAMPUNG BERSERI ASTRA” TERHADAP SOSIAL EKONOM DI JORONG TABEK NAGARI TALANG BABUNGO KABUPATEN SOLOK - Mukhliswal "; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study examines the Impact of the Kampung Berseri Asta (KBA) Program on the Socio-Economic in Jorong Tabek, Nagari Talang Babungo, Solok Regency. Kampung Berseri Astra (KBA) is one of the Corporate Social Responsibility (CSR) programs of PT. Astra International Tbk. which is implemented in people’s lives by using four main programs, namely: Education, health, economy, and the environment in Jorong Tabek. The Kampung Berseri Asta (KBA) Program is a guidance, improvement program to create smart, healthy, productive and clean villages by utilizing the potential of the village. The research method used is descriptive quantitative method, the authors distributed questionnaires to obtain data about the impact of the Astra series village program on the socio-economic community in Jorong Tabek with a sample of 86 people with cluster  sampling techniques. The results of this study indicate that Kampung Berseri Asta (KBA) Program from PT. Astra International Tbk. give impact and change from the Astra Sereri Village Program (KBA) which has been seen from the flagship program in four main pillars namely, Education, Health, Economy and Living Environment. The Kampung Berseri Asta (KBA) Program) in Jorong Tabek has succeeded in making Jorong Tabek a fostered village, that success cannot be separated from the cooperation of all parties, both the community, managers and Astra. Keyword : Kampung Berseri Astra, Program, Impact